Fabrication and characterization of composite sealants for low temperature (600-650°C) SOFCs - Lim, H.-Y.; Kim, H.; Choi, S.-H.; Kim, H.-R.; Son, J.-W.; Lee, H.-W.; Lee, J.-H. (2008)
A proper sealant for low temperature SOFCs should show zero or low leak rates to avoid direct mixing of the fuel and oxidant gases or leakage of fuel gas during the operation of SOFCs. Furthermore, it should be chemically and/or mechanically stable in both oxidizing and reducing environments and chemically compatible with other fuel cell components. In the present work, we developed a novel compressed seal gasket of glass-based composite reinforced with ceramic particulate particles, which can efficiently control the viscous flow of glass matrix as well as the crystallization of glass phase. This novel sealing gasket showed excellent gas tightness under very low compressive load which would be suitable for the operation of SOFCs in the temperature range 600~650°C.
Keywords: Ceramic particulates; Composite sealants; Compressive loads; Fuel cell components; Fuel gas; Gas leakage; Gastightness; Glass composite; Glass matrices; Glass phase; Glass-based composites; Leak rate; Low temperatures; Mechanically stable; Reducing environment; SOFC; Temperature range; Asphalt pavements; Gases; Gaskets; Glass; Sealants; Solid oxide fuel cells (SOFC); Leakage (fluid)